A Genome-Wide Scan for Childhood Obesity–Associated Traits in French Families Shows Significant Linkage on Chromosome 6q22.31-q23.2 - Meyre, David; Lecoeur, Cécile; Delplanque, Jérôme; Francke, Stephan; Vatin, Vincent; Durand, Emmanuelle; Weill, Jacques; Dina, Christian; Froguel, Philippe (Diabetes (New York, N.Y.), 2004)
A Genome-Wide Scan for Childhood Obesity–Associated Traits in French Families Shows Significant Linkage on Chromosome 6q22.31-q23.2 David Meyre 1 , Cécile Lecoeur 2 , Jérôme Delplanque 1 , Stephan Francke 1 , Vincent Vatin 1 , Emmanuelle Durand 1 , Jacques Weill 1 3 , Christian Dina 1 and Philippe Froguel 1 2 1 Centre National de la Recherche Scientifique (CNRS) Unité Mixte de Recherche (UMR) 8090, Institute of Biology of Lille, Pasteur Institute, Lille, France 2 Hammersmith Genome Centre and Genomic Medicine, Imperial College, London, U.K 3 Department of Pediatrics, Jeanne de Flandres Hospital, Lille, France Address correspondence and reprint requests to Philippe Froguel, CNRS UMR 8090, Institute of Biology, Institute Pasteur of Lille, 1, rue du Pr. Calmette, B.P.447 59021 Lille Cedex, France. E-mail: froguelatmail-good.pasteur-lille.fr Abstract We conducted a genome-wide search for childhood obesity–associated traits, including BMI ≥95th percentile (PCT95), 97th percentile (PCT97), and 99th percentile (PCT99) as well as age of adiposity rebound (AAR), which corresponds to the beginning of the second rise in childhood adiposity. A set of 431 microsatellite markers was genotyped in 506 subjects from 115 multiplex French Caucasian families, with at least one child with a BMI ≥95th percentile. Among these 115 pedigrees, 97 had at least two sibs with a BMI ≥95th percentile. Fine-mapping was performed in the seven most positive loci. Nonparametric multipoint analyses revealed six regions of significant or suggestive linkage on chromosomes 2q33.2-q36.3, 6q22.31-q23.2, and 17p13 for PCT95, PCT97, or PCT99 and 15q12-q15.1, 16q22.1-q24.1, and 19p13.3-p13.11 for AAR. The strongest evidence of linkage was detected on chromosome 6q22.31 for PCT97 (maximum likelihood score: 4.06) at the marker D6S287. This logarithm of odds score meets genome-wide significance tested through simulation (empirical genome-wide P = 0.01 [0.0027–0.0254]). Six independent ge-nome scans in adults have reported quantitative trait loci on 6q linked to energy or glucose homeostasis-associated phenotypes. Possible candidate genes in this region include SIM1 , MCHR2 , and PC-1 . AAR, age of adiposity rebound LOD, logarithm of odds MLB, maximum likelihood binomial MLS, maximum likelihood score Footnotes Accepted November 20, 2003. Received September 5, 2003. DIABETES